2012
DOI: 10.1002/cphc.201200037
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electron Transfer from CdSe/ZnS Quantum Dots to TiO2 Nanoparticles: Size Dependence at the Single‐Molecule Level

Abstract: Electron transfer (ET) kinetics of CdSe/ZnS core/shell quantum dots (QDs) on bare coverslips and a TiO(2) nanoparticle-coated thin film has been investigated at the single-molecule level. The QDs prepared have three different diameters of 3.6, 4.6, and 6.4 nm. The trajectories of fluorescence intensity are acquired with respect to the arrival time. The on-time events and subsequent fluorescence lifetimes are shorter with decreasing size. Given the lifetime measurements for QDs on glass and TiO(2), the rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(243 reference statements)
1
2
0
Order By: Relevance
“…It is seen that as compared to the hole, the electron is preferentially localized in the shell region by a factor of 3. This trend is consistent with experimental observations. ,, For example, Zhu et al have found that there is an optimum shell thickness for controlling the charge separation in CdSe/ZnS QDs . In addition, they have also observed preferential localization of the electron in the shell material for these QDs .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It is seen that as compared to the hole, the electron is preferentially localized in the shell region by a factor of 3. This trend is consistent with experimental observations. ,, For example, Zhu et al have found that there is an optimum shell thickness for controlling the charge separation in CdSe/ZnS QDs . In addition, they have also observed preferential localization of the electron in the shell material for these QDs .…”
Section: Resultssupporting
confidence: 85%
“…Abdellah et al have also found that there is an optimal shell thickness for achieving efficient charge transfer from the core/shell quantum dot system . As a consequence of this, core/shell quantum dots have been coupled with materials such as TiO 2 in order to modify the electron transfer rates. , Zhu et al have engineered core/shell QDs to increase the charge separation and decrease the charge recombination . The results in Figures – provide additional metrics that confirm these experimental observations.…”
Section: Resultsmentioning
confidence: 70%
“…Fluorescence decays were recorded by using the timecorrelated single-photon counting technique as reported elsewhere. 45 1 H NMR and 13 C NMR spectra were recorded on a Bruker DPX 400 MHz NMR spectrometer in deuterated solvents. All NMR spectra were assigned, and the chemical shis are reported in ppm downeld relative to the chemical shi.…”
Section: Methodsmentioning
confidence: 99%